How dialogues facilitate high school students’ responses to poetry - Daniela Cavalli (Universitat Autònoma de Barcelona, 2019)
Drawing from a case study on students’ responses to poetry in a Catalan public high school, this article shows how dialogues facilitate students’ aesthetic experiences. The study sheds light on how one on one, and small group conversations that occurred in interview situations -in connection with classroom activity- mediated these responses. As a way to understand dialogical mediation and the affordances of poems in student-reader activity, the analysis connects a sociocultural understanding of literary reading to readers’ response theory and its empirical study. Results show that in joint meaning-making activity students (a) live through emotional experiences and (b) respond to distinctive poetic devices, which, in turn, create opportunities (c) for their poetic literacy, and (d) ideological becoming (Bakhtin, 1981).